Phase-Specific Plasticity of Synaptic Structures in the Somatosensory Cortex of Living Mice during Neuropathic Pain. Issue 1 (9th November 2011) - Kim, Sun Kwang; Kato, Go; Ishikawa, Tatsuya; Nabekura, Junichi
Background: Postsynaptic dendritic spines in the cortex are highly dynamic, showing rapid morphological changes including elongation/retraction and formation/elimination in response to altered sensory input or neuronal activity, which achieves experience/activity-dependent cortical circuit rewiring. Our previous long-term in vivo two-photon imaging study revealed that spine turnover in the mouse primary somatosensory (S1) cortex markedly increased in an early development phase of neuropathic pain, but was restored in a late maintenance phase of neuropathic pain. However, it remains unknown how spine morphology is altered preceding turnover change and whether gain and loss of presynaptic boutons are changed during neuropathic pain. Findings: Here we used short-term (2-hour) and long-term (2-week) time-lapse in vivo two-photon imaging of individual spines and boutons in the S1 cortical layer 1 of the transgenic mice expressing GFP in pyramidal neurons following partial sciatic nerve ligation (PSL). We found in the short-term imaging that spine motility (A length per 30 min) significantly increased in the development phase of neuropathic pain, but returned to the baseline in the maintenance phase. Moreover, the proportion of immature (thin) and mature (mushroom) spines increased and decreased, respectively, only in the development phase. Long-term imaging data showed that formation and elimination of boutons moderately increased and decreased, respectively, during the first 3 days following PSL and was subsequently restored. Conclusions: Our results indicate that the S1 synaptic structures are rapidly destabilized and rearranged following PSL and subsequently stabilized in the maintenance phase of neuropathic pain, suggesting a novel therapeutic target in intractable chronic pain.